Initial experience with xenograft bioconduit for the treatment of complex prosthetic valve endocarditis. (July 2017) - Roubelakis, Apostolos; Karangelis, Dimos; Sadeque, Syed; Yanagawa, Bobby; Modi, Amit; Barlow, Clifford W; Livesey, Steven A; Ohri, Sunil K
Introduction: The treatment of complex prosthetic valve endocarditis (PVE) with aortic root abscess remains a surgical challenge. Several studies support the use of biological tissues to minimize the risk of recurrent infection. We present our initial surgical experience with the use of an aortic xenograft conduit for aortic valve and root replacement. Methods: Between October 2013 and August 2015, 15 xenograft bioconduits were implanted for complex PVE with abscess (13.3% female). In 6 patients, concomitant procedures were performed: coronary bypass (n=1), mitral valve replacement (n=5) and tricuspid annuloplasty (n=1). The mean age at operation was 60.3±15.5 years. The mean Logistic European system for cardiac operating risk evaluation (EuroSCORE) was 46.6±23.6. The median follow-up time was 607±328 days (range: 172-1074 days). Results: There were two in-hospital deaths (14.3% mortality), two strokes (14.3%) and seven patients required permanent pacemaker insertion for conduction abnormalities (46.7%). The mean length of hospital stay was 26 days. At pre-discharge echocardiography, the conduit mean gradient was 9.3±3.3mmHg and there was either none (n=6), trace (n=6) or mild aortic insufficiency (n=1). There was no incidence of mid-term death, prosthesis-related complications or recurrent endocarditis. Conclusions: Xenograft bioconduits may be safe and effective for aortic valve and root replacement for complex PVE with aortic root abscess. Although excess early mortality reflects the complexity of the patient population, there was good valve hemodynamics, with no incidence of recurrent endocarditis or prosthesis failure in the mid-term. Our data support the continued use and evaluation of this biological prosthesis in this high-risk patient cohort.